2020
DOI: 10.1186/s12913-020-05444-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of care in sick child services at health facilities in Ethiopia

Abstract: Background: Quality of care depends on system, facility, provider, and client-level factors. We aimed at examining structural and process quality of services for sick children and its association with client satisfaction at health facilities in Ethiopia. Methods: Data from the Ethiopia Service Provision Assessment Plus (SPA+) survey 2014 were used. Measures of quality were assessed based on the Donabedian framework: structure, process, and outcome. A total of 1908 mothers or caretakers were interviewed and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…However, the general health post readiness had no association with awareness and coverage of pentavalent-3 immunisation, but a negative association with care-seeking for childhood suspected pneumonia and other illnesses. Studies in Haiti and Ethiopia have shown absence of association between readiness of primary healthcare facilities for sick child care and caregivers’ utilisation and satisfaction to the respective services 40 58. The lack of consistent positive association may be linked to the dominating low level of health post preparedness.…”
Section: Discussionmentioning
confidence: 98%
“…However, the general health post readiness had no association with awareness and coverage of pentavalent-3 immunisation, but a negative association with care-seeking for childhood suspected pneumonia and other illnesses. Studies in Haiti and Ethiopia have shown absence of association between readiness of primary healthcare facilities for sick child care and caregivers’ utilisation and satisfaction to the respective services 40 58. The lack of consistent positive association may be linked to the dominating low level of health post preparedness.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies carried out in private and public health facilities in Uganda and other African countries found that 7-24% children testing positive for malaria never received the correct malaria medicine [46,47]. In a study from Nigeria, over 85% of children with watery diarrhea were given unnecessary antibiotics, while in a study from Ethiopia, the assessment, as well as treatment of children for cough, fever, and diarrhea in clinics was of poor quality [48,49]. In our study, it is probable that the health workers were able to diagnose the conditions using the knowledge they had from their professional training since the presentation of the conditions remains the same.…”
Section: Discussionmentioning
confidence: 98%
“…This scenario could indicate that Open access many care-seeking sick children were not getting the care they required, at least not at the health post. 35 The lack of essential medicines might be a reason for some referrals of children with non-severe diseases, which otherwise may be treated at the first-level health facility. 32 36 This condition might also impose caregiver for unnecessary social and economic costs incurred by referrals of children with non-severe illnesses.…”
Section: Discussionmentioning
confidence: 99%